Preinjury physical frailty and cognitive impairment among geriatric trauma patients determine postinjury functional recovery and survival. Issue 2 (February 2016) - Maxwell, Cathy A.; Mion, Lorraine C.; Mukherjee, Kaushik; Dietrich, Mary S.; Minnick, Ann; May, Addison; Miller, Richard S.
Abstract : BACKGROUND: Injury is an external stressor that often initiates a cycle of decline in many older adults. The influence of physical frailty and cognitive decline on 6-month and 1-year outcomes after injury is unreported. We hypothesized that physical frailty and cognitive impairment would be predictive of 6-month and 1-year postinjury function and overall mortality. METHODS: The sample involved patients who are 65 years or older admitted to a Level I trauma center between October 2013 and March 2014 with a primary injury diagnosis. Surrogates of 188 patients were interviewed within 48 hours of hospital admission to determine preinjury cognitive and physical frailty impairments using brief screening instruments. Follow-up was completed on 172 patients at 6 months and 176 patients at 1 year to determine posthospitalization status and outcomes. Data analysis involved frequencies, measures of central tendency, χ 2 analyses, linear and logistic regression. RESULTS: The mean age of the patients was 77 years. The median Injury Severity Score (ISS) was 10. The mechanism of injury involved falls from standing (n = 101, 54%). Preinjury vulnerabilities included cognitive impairment (AD8 Dementia Screen [AD8] score ≥ 2, n = 93, 50%) and physical frailty (Vulnerable Elders Survey [VES-13] score ≥ 4, n = 94, 50%). Overall, median physical frailty scores did not return to baseline in the majority of survivors at 1 year. Multivariate regression analysis revealed that preinjury cognitive impairment (6 months, AD8, β = −0.20, p = 0.002) and preinjury physical frailty (6 months, Barthel Index, β = 0.60, p < 0.001; 1 year, Barthel Index, β = 0.52, p < 0.001) are independently associated with physical function (frailty). Multivariate logistic regression analysis revealed that age (odds ratio [OR], 1.09; 95% confidence interval [CI], 1.04–1.14), injury severity (OR, 1.07; 95% CI, 1.02–1.12), and preinjury physical frailty (OR, 1.28; 95% CI, 1.14–1.47) are independently associated with overall mortality at 1 year. CONCLUSION: Preinjury physical frailty is the predominant predictor of postinjury functional status and mortality in geriatric trauma patients. Identification of frailty and appropriate follow-up are crucial for decision making by providers, patients, and family caregivers. LEVEL OF EVIDENCE: Prognostic study, level II. Abstract : Supplemental digital content is available in the text.